Penelitian Pendahuluan: Permen Rendah Gula Dari Sari Buah Delima-Buah Surga Sebagai Alternatif Mengatasi Anemia Remaja - Alfiah, Elma; Yusuf, Andi Mukramin; Umami, Zakia (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2023)
WHO reported in 2016 that the prevalence of anemia among women was 32.8%. One of the causes for anemia is the deficiency of iron in the human blood cells. Pomegranate has the potential to increase iron status in cells and functional iron. The general objective of this study was to determine the best formulation of pomegranate candy based on the results of its sensory tests and nutritional content. This study was divided into 4 stages: pomegranate extraction, preliminary trial and error, sensory test, and nutritional content test. The sensory test results showed that the three candy formulations with various gelatin compositions had the same sensory properties. The smell and appearance of all candy formulations were classified as normal, the colors of the candy were identified as white and brown, and the taste of the candy was identified as slightly sour with a chewy texture and a solid shape. The candy formulation with the highest gelatin content had the highest iron and protein content, as well as the lowest water content, and longer shelf life. This makes candy with the highest gelatin content determined to be the best formula considering its higher ability to overcome anemia.  Keyword - Anemia, Candy, Fruit of Heaven, Pomegranate